The Efficacy of Solifenacin Added to Α-Adrenergic Antagonists in the Treatment of Lower Urinary Tract Symptoms in Males with Benign Prostate Hyperplasia (The Iraqi Experience) - AL-Hamdani, Nibbras I.; Daraji, Saad D.; Zeki, Ali W. (Journal of the Faculty of Medicine Baghdad, 2015)
symptoms/Benign prostate hyperplasia (LUTS/BPH) raises the possibility that a combination of α-adrenergic blocker therapy with anticholinergic therapy could both reduce the risk of retention or deteriorating bladder function and also add to the treatment of the remaining obstructive symptoms of LUTS/BPH. Objective: Is to investigate the efficacy and tolerability of 5mg solifenacin in the treatment of lower urinary tract symptoms in patients with benign prostatic hyperplasia in combination with an alpha-blocker. Patients and methods: This is a prospective study of 29 patients with benign prostatic hyperplasia already on alpha-blockers, given solifenacin 5mg once daily. International prostate symptom score (IPSS), patient micturition diaries, quality of life index (QOL), post-void residual urine (PVR) and maximum flow rate (Qmax) and urodynamic findings were recorded before and after three months of therapy. Adverse events were documented. Results: At baseline, the total IPSS was 15.3+5.7 that decreased to 10.8+5.3 (net change -4.5, P value <0.03). Although the mean IPSS for voiding symptoms was not significant, significant change was noted in the storage symptoms (from 8.4+2.4 to 5.1+2.5 P value <0.001). The quality of life index was significantly improved for the patients enrolled from 4.4+1.4 to 2.8+1.3. The maximum flow rate increased from 11.6+5.7 to 14.3+6.1 with a net change of +2.7 ml/sec (P value <0.01) ml/sec. Two patients stopped the medication because of side effects. The side effects included dry mouth (17.24%) followed by constipation (6.90%) then headache and blurred vision (3.45%) for each. No urine retention developed in any patient. Conclusions: The use of solifenacin in selected cases in the treatment of LUTS in patients with BPH is highly effective addition to alpha-blockers